Functionalized NiFe2O4/mesopore silica anchored to guanidine nanocomposite as a catalyst for synthesis of 4H-chromenes under ultrasonic irradiation - Mohammadi, Somaye; Mohammadi, Zeinab (Journal of Composites and Compounds, 2021)
A synergetic effect of nanocatalyst and ultrasonic irradiation was examined for the synthesis of 4H-chromenes from benzaldehyde, cyclohexanone, and malononitrile. It was observed this contributory improved the reaction that was used for the synthesis of the highly pure products in short reaction times and highest yields. The nanocomposite includes the guanidine anchored on to magnetic NiFe2O4 nanoparticles were used as the active base nanocatalyst for the sonication synthesis of 4H-chromenes compounds. The product was separated with simple filtration and purify with recrystallization by ethanol solvent. After completing the reaction, a nanocatalyst was collected and reused in 6 runs of model reaction. This nanocomposite has a magnetic core and a very active base surface area shell. The nanocatalyst was provided by the simple technique and identified by using FT-IR spectrum, scanning electron microscopy (SEM), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), and Brunauer–Emmett–Teller (BET). This nanocomposite was used for the synthesized various derivatives of 4H-chromenes under ultrasonic irradiation. The organic products were identified by FT-IR and 1H-NMR.